Fintech and Operational Efficiency: Empirical Evidence from Indonesia’s Banking Sector - Burhanuddin; Andi Mustika Amin; Hery Maulana Arif (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2025)
This study investigates the impact of financial technology (Fintech) adoption on the operational efficiency of commercial banks listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023. Employing a quantitative causal-associative method and panel data regression analysis, the research explores how Fintech-driven digital transactions influence banks’ cost structures and efficiency ratios. Data were drawn from annual financial statements and digital transaction reports of four major banks: PT Bank Rakyat Indonesia, PT Bank Negara Indonesia, PT Bank Mandiri, and PT Bank Central Asia. The results reveal that Fintech adoption has a significant and negative effect on both Operating Cost to Operating Income (OCOI) and Cost-to-Income Ratio (CIR), indicating that increased digital transaction activity leads to lower operational costs and improved efficiency. These findings demonstrate that Fintech plays a pivotal role in enhancing banking performance by reducing transaction expenses, optimizing resource allocation, and promoting service accessibility. The study contributes to academic discourse and provides strategic insights for banking practitioners and regulators to strengthen digital transformation policies and foster inclusive Fintech adoption in Indonesia’s financial ecosystem.